The Potential of Mobile Technologies for (English) Language Learning in Nepal - Shrestha, Prithivi (Journal of NELTA, 2012)
Mobile technologies have proven to be beneficial to language learners in both developed and developing countries around the world. However, they do not seem to have been exploited for language learning in Nepal although they have already been used for other purposes and their use is rapidly growing. This article proposes a number of ways that mobile technologies, particularly, mobile phones, can be deployed for language learning and teacher professional development. A number of potential challenges are also discussed. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6134 NELTA 2011; 16(1-2): 107-113